1996
DOI: 10.2337/diacare.19.11.1185
|View full text |Cite
|
Sign up to set email alerts
|

Metformin's Effects on Glucose and Lipid Metabolism in Patients with Secondary Failure to Sulfonylureas

Abstract: Metformin is an effective, safe, and well-tolerated treatment that improves metabolic control and favorably modifies secondary clinical alterations due to insulin resistance, such as arterial hypertension, overweight, and hyperlipidemia, in obese patients with NIDDM suffering from secondary failure to sulfonylureas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
2
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 25 publications
4
25
2
1
Order By: Relevance
“…Significant reduction of HbA 1C (-0.79 ± 1.18%) was observed after 6 months administration of metformin. While an improvement of lipid metabolism in European and American populations has been reported [2,6,13,14], no such improvement has been reported in a Japanese one [4,5]. This may be attributable to the difference in the setting of the therapeutic dosage, BMI, insulin secretion capacity, and 'thrifty' genetic factors between Japanese and American / European populations.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Significant reduction of HbA 1C (-0.79 ± 1.18%) was observed after 6 months administration of metformin. While an improvement of lipid metabolism in European and American populations has been reported [2,6,13,14], no such improvement has been reported in a Japanese one [4,5]. This may be attributable to the difference in the setting of the therapeutic dosage, BMI, insulin secretion capacity, and 'thrifty' genetic factors between Japanese and American / European populations.…”
Section: Discussionmentioning
confidence: 64%
“…Reports on the improvement of blood pressure have been published by Landin et al [13] and Fanghanel et al [14] and a significant reduction in SBP and DBP was also observed. Meanwhile, no weight change was observed during these studies.…”
Section: Discussionmentioning
confidence: 82%
“…8 Metformin improves insulin sensitivity, decreases insulin levels, and controls hyperglycemia. 10,11 In addition, metformin improves lipid profiles and lowers blood pressure in both patients and animal models with impaired glucose tolerance and type 2 diabetes mellitus. [11][12][13][14] In addition to its insulin-sensitizing effects, metformin has also been shown to have direct vascular effects.…”
mentioning
confidence: 99%
“…10,11 In addition, metformin improves lipid profiles and lowers blood pressure in both patients and animal models with impaired glucose tolerance and type 2 diabetes mellitus. [11][12][13][14] In addition to its insulin-sensitizing effects, metformin has also been shown to have direct vascular effects. 15,16 Thus, it is currently unclear whether the hypotensive effect of metformin is due to a direct vascular effect, its ability to improve insulin sensitivity, its ability to improve lipids, or a combination of mechanisms.…”
mentioning
confidence: 99%
“…One logical explanation for this large effect is that metformin does more than lower blood glucose. A prospective study noted favourable changes in lipids as well as in blood pressure 20 . The large risk reduction associated with MI makes the use of metformin economical.…”
Section: Metforminmentioning
confidence: 99%